Solitons train in nonlocally nonlinear system with oscillatory responses. (March 2023) - Liang, Guo; Shu, Fangjie; Qiao, Hongzhen; Cheng, Wenjing
Abstract: We introduced a class of solitons train in nonlocally nonlinear system with sin-oscillatory response. The solitons train can be compose of arbitrary number of sub-beams. Each sub-beam will be trapped by the light self-induced waveguide. Under the boundary force of the self-induced waveguide, an optical beam with transverse velocity can exhibits the Snake-shaped trajectory, or can evolve into the chaoticon-shaped pattern with invariant statistic width. All the solitons train are stable, which obeys an inverted Vakhitov–Kolokolov stability criterion.